1996
DOI: 10.1121/1.416410
|View full text |Cite
|
Sign up to set email alerts
|

Filtration technique enhanced by electro-acoustic methods

Abstract: Results from an experimental study of electric and/or ultrasonic field assisted filtration are presented. Both electric and ultrasonic fields can reduce fouling of the filtration medium and have significant influence on filtration capacity. The extent of filtration improvement is affected mostly by particle size, surface charge, acoustic frequency, and field strengths. Theoretical examinations of the use of electric field and/or ultrasonic field to enhance filtration efficiency were laid out. Some aspects rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The filtration of flocculated suspensions under this mechanism proved to be consistent with the results obtained by Tuori (1996), who studied the filtration of an aqueous pyrite suspension, under intermittent ultrasound effect. It was found that the performance of the system was superior to that obtained under conventional filtration.…”
Section: Vacuum Ultrasonic Filtrationsupporting
confidence: 77%
“…The filtration of flocculated suspensions under this mechanism proved to be consistent with the results obtained by Tuori (1996), who studied the filtration of an aqueous pyrite suspension, under intermittent ultrasound effect. It was found that the performance of the system was superior to that obtained under conventional filtration.…”
Section: Vacuum Ultrasonic Filtrationsupporting
confidence: 77%